Mental Health Challenges in the Post Pandemic Era - Gupta, Pulkita (AG Volumes, 2025)
The impact of the COVID-19 epidemic on mental health has been well documented. But in the latter stages of the epidemic and after its formal conclusion, very few research looked into mental health. Furthermore, not much is known about the psychological toll that the pandemic and various post-pandemic global issues have had on individuals. This article reviews the many research that have been conducted on mental health concerns in the post-pandemic era. It came to the conclusion that a worldwide mental health crisis has been brought on by the COVID-19 pandemic, placing additional burden on already brittle support networks, especially in low- and middle-income (LMIC) nations. More stress is experienced by mental health professionals (MHPs), and treatment efforts are hampered by pervasive misinformation. People and families have been profoundly impacted by the loss of organised settings like businesses and schools, particularly women and young people. There are many people who have persistent symptoms of depression, anxiety, and panic. Psychological anguish is higher in vulnerable populations, such as individuals with metabolic diseases. Long-term mental health risks must be reduced, and post-pandemic psychological resilience must be promoted, by ensuring continuity of treatment via telepsychiatry, focused therapies, and comprehensive legislative changes.